1992
DOI: 10.1677/joe.0.1340127
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor stimulates production of insulin-like growth factor-binding protein-1 in human granulosa-luteal cells

Abstract: Insulin-like growth factor-I (IGF-I) enhances and epidermal growth factor (EGF) inhibits gonadotrophin-induced aromatization in granulosa cells. Our previous studies have shown that human ovarian granulosa cells synthesize insulin-like growth factor-binding protein-1 (IGFBP-1) which inhibits IGF-stimulated DNA synthesis. The present study addresses the effect of EGF and gonadotrophins in the regulation of IGFBP-1 release by human granulosa cells cultured in serum-free medium. At concentrations of 1-100 microgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Thus, IGFBP-1 may play an important role in cell replication. In support of such a role, it has been shown that IGFBP-1 is the most highly induced early growth response gene expressed in regenerating liver (Mohn et al, 1990;Ghahary et al, 1992) and EGF, which is believed to play a role in liver regeneration, increases IGFBP-1 synthesis in human hepatoma cells (Angervo et al, 1992). All of these studies indicate the importance of accounting for these parameters in studies of IGFBP-1 regulation and emphasise the complexity of the mechanisms controlling IGFBP-1.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, IGFBP-1 may play an important role in cell replication. In support of such a role, it has been shown that IGFBP-1 is the most highly induced early growth response gene expressed in regenerating liver (Mohn et al, 1990;Ghahary et al, 1992) and EGF, which is believed to play a role in liver regeneration, increases IGFBP-1 synthesis in human hepatoma cells (Angervo et al, 1992). All of these studies indicate the importance of accounting for these parameters in studies of IGFBP-1 regulation and emphasise the complexity of the mechanisms controlling IGFBP-1.…”
Section: Discussionmentioning
confidence: 96%
“…The oocytes present in the milieu of FF, which is rich in hormones such as progesterone, FSH and luteinizing hormone (LH), are associated with follicular maturation and oocyte development [17]. Epidermal growth factor (EGF) [2], insulin-like growth factor (IGF) and transforming growth factor (TGF) [6] have been detected in follicular fluid.…”
Section: Discussionmentioning
confidence: 99%
“…However, a limitation of this study is that we are unable to attribute fertilization to oocyte quality only, although we Fig. 2 Spectral counts of heparan sulfate proteoglycan perlecan in the follicular fluids containing fertilized oocytes (fFF) and non-fertilized oocytes (nfFF) in each patient (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) tried to minimize the influence of sperm quality using ICSI. An increased number of samples would enable the use of a proteomics analysis to identify distinctive biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…EGF has been reported to exhibit luteotropic effects on cultured human GL cells by augmenting basal and hCG-and PGE 2 -stimulated progesterone production [56]. It also stimulates IGFBP-1 production in these cells [57]. As immunoreactive EGF protein has been localized to the human preovulatory follicles [58] and CL [59], it may have a physiological role in regulating the formation of the CL and FS production in the human ovary.…”
Section: Discussionmentioning
confidence: 99%